2018
DOI: 10.1002/eco.1975
|View full text |Cite
|
Sign up to set email alerts
|

Minor contribution of overstorey transpiration to landscape evapotranspiration in boreal permafrost peatlands

Abstract: Evapotranspiration (ET) is a key component of the water cycle, whereby accurate partitioning of ET into evaporation and transpiration provides important information about the intrinsically coupled carbon, water, and energy fluxes. Currently, global estimates of partitioned evaporative and transpiration fluxes remain highly uncertain, especially for high‐latitude ecosystems where measurements are scarce. Forested peat plateaus underlain by permafrost and surrounded by permafrost‐free wetlands characterize appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…Lower T birch /ET eco values in Kevo could also result from a disproportionately higher contribution from the understorey in a sparser woodland (i.e., higher below-canopy incident radiation compared to Abisko). The values of of T birch /ET eco at the two sites are consistent with the generally low contribution of overstorey to total evapotranspiration in subarctic and northern boreal forests (Iida et al, 2009;Ikawa et al, 2015;Kelliher et al, 1997;Lafleur, 1992;Warren et al, 2019). However, in Kevo, our estimates of upscaled evapotranspiration from individual ecosystem components (i.e., mountain birch, understorey shrubs, and lichen heath) yielded growing season values, which were still far from total ecosystem evapotranspiration measured by eddy covariance (Table 4, cf.…”
Section: Contribution Of Mountain Birch Transpiration To Ecosystem supporting
confidence: 79%
“…Lower T birch /ET eco values in Kevo could also result from a disproportionately higher contribution from the understorey in a sparser woodland (i.e., higher below-canopy incident radiation compared to Abisko). The values of of T birch /ET eco at the two sites are consistent with the generally low contribution of overstorey to total evapotranspiration in subarctic and northern boreal forests (Iida et al, 2009;Ikawa et al, 2015;Kelliher et al, 1997;Lafleur, 1992;Warren et al, 2019). However, in Kevo, our estimates of upscaled evapotranspiration from individual ecosystem components (i.e., mountain birch, understorey shrubs, and lichen heath) yielded growing season values, which were still far from total ecosystem evapotranspiration measured by eddy covariance (Table 4, cf.…”
Section: Contribution Of Mountain Birch Transpiration To Ecosystem supporting
confidence: 79%
“…Understory vegetation is composed of a carpet of Sphagnum moss. A detailed description of the fen vegetation can be found in Bocking, Cooper, and Price (2017) AET was measured continuously and recorded at half hour intervals, 4 m above the ground surface using an eddy covariance (EC) system, and summed to daily values, following similar approaches used in boreal peatlands (Brown et al, 2010;Warren et al, 2018;Wells et al, 2017). The EC system consisted of a 3D sonic anemometer (Gill Windmaster Pro, Gill Instruments, Lymington, UK) and a closed-path infrared gas (CO 2 /H 2 O) analyser (LI-7200, LICOR Inc., Lincoln, Nebraska) sampled at 20Hz.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Air temperature and relative humidity were measured 2m above the surface (HMP35C, Vaisala, Helsinki, AET was measured continuously and recorded at half hour intervals, 4 m above the ground surface using an eddy covariance (EC) system, and summed to daily values, following similar approaches used in boreal peatlands (Brown et al, 2010;Warren et al, 2018;Wells et al, 2017). Air temperature and relative humidity were measured 2m above the surface (HMP35C, Vaisala, Helsinki, AET was measured continuously and recorded at half hour intervals, 4 m above the ground surface using an eddy covariance (EC) system, and summed to daily values, following similar approaches used in boreal peatlands (Brown et al, 2010;Warren et al, 2018;Wells et al, 2017).…”
Section: Micrometerological Variablesmentioning
confidence: 99%
“…Observational studies have reported values of the transpiration-to-evapotranspiration ratio (T/ET) spanning a wide range of values globally, from ∼60%±25%; (Coenders-Gerrits et al 2014) up to ∼85% ± 5%; (Jasechko et al 2013) with several recent studies reporting different estimates (Coenders-Gerrits et al 2014, Wang et al 2014, Good et al 2015, Berkelhammer et al 2016, Zhou et al 2016, Wei et al 2017. T/ET in boreal peatland ecosystems has been also found to be as low as 1% (Warren et al 2018). Most observational-based estimates were derived using either water isotope data (Jasechko et al 2013) or eddy-covariance flux tower data (Zhou et al 2016).…”
Section: Introductionmentioning
confidence: 99%